Pendekatan Alternatif Animasi 2d Dalam Media Edukatif Peningkatan Pariwisata Kota Tua Kali Besar Barat - Viecel Altisya; Huddiansyah (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Kali Besar, an important port in the colonial era in Kota Tua, preserves a rich history with a variety of social, economic, and cultural transformations. However, the history of Kali Besar Barat is still less known to modern society. Through an interesting visual and educational approach, the project depicts historical buildings on Kali Besar Barat, as well as a chronological explanation of the history of the transitional functions of each building. The methods used included live observations, interviews with historians and animator, as well as literary studies. The result of this research is an interesting and educational 2D animation that is expected to introduce Kali Besar Barat to the public, especially young adults, and contribute to the development of animation-based educational media. In addition to serving as a learning medium, this 2D animation is expected to increase public awareness of the importance of preserving historical areas in Jakarta’s Old Town. By integrating accurate historical data with clear and engaging visual presentation, this project seeks to present historical narratives that are easy to understand and relevant to contemporary contexts, thereby offering an effective and sustainable alternative medium for history education.